TEACHERS’ ELICITATION: INVITING STUDENTS TO SPEAK - Bustami Usman; Nour Ayouni; Iskandar Abdul Samad; Siti Sarah Fitriani (Universitas Islam Sultan Agung, 2018)
This study describes the implementation of teachers’ elicitation in speaking class of English Department of Ar-raniry Islamic State University. It attempts to investigate types of elicitation used by the lecturers in speaking class and the most frequent type. The participants of this study were five lecturers of speaking classes and hence ten teaching sessions were video-recorded and transcribed in order to analyze lecturers’ utterance that indicates teachers’ elicitation. Quantitative and qualitative method were employed where the data were obtained from observation and interview by means of video recorder, field-notes, observation sheet and interview guide. Technique of data analysis was followed Miles’s & Huberman’s (1992) model including data reduction, data display, and conclusion. The results of this study revealed six types of elicitations; elicit:inform, elicit:confirm, elicit:agree, elicit:commit, elicit:repeat, and elicit:clarify were used by the lecturers in teaching speaking. It is also found elicit:inform was the most frequent type of elicitation used which reached 72.23%. This indicates that the lecturers frequently used elicitation to invite students to speak.